The nature and challenges of street sweeping in Ado-Ekiti (2014)
"This study examined the nature of street sweeping, the composition of litters, the socio-economic and health status of street sweepers and the public perception of the benefits and challenges of street sweeping in Ado-Ekiti. Primary data were obtained through direct personal observation, questionnaire administration and in-depth interview while secondary data were sourced from published and unpublished documents. Purposive and random sampling methods were adopted in the selection of respondents for questionnaire administration. Four types of structured questionnaire were designed and administered separately to: 103 (20%) of the street sweepers along the 21 swept streets; 193 (5%) buildings along the 21 streets; 14 officials of the Ekiti State Waste Management Authority involved in the street sweeping programme, and 42 pedestrians (female and male) along the 21 swept streets. Descriptive statistics were used to analyse the data collected. Findings revealed that all the street sweepers were females and casual workers. Sediments/broken blocks/sand/gravel (18.8%), plastics (16.6%), nylon/polythene (16.6%), leaves/wood/grass (15.0%), food wastes (12.6%), paper (9.9%), aluminum cans/metals/glass (5.3%), and miscellaneous (5.2%) constituted the street litters. The sweepers suffered from joint pain (96.1%), catarrh (91.3%), cough (83.5%) eye infection (70.8%) asthma (46.6%) and malaria (31.1%). Inadequate personnel, insufficient tools and equipment, poor remuneration, stigmatisation, exposure to accidents and harassment were the challenges faced by the sweepers. The benefits created by the street sweeping programme are: city beautification and aesthetics (74.6%); employment opportunity (16.6%); improved urban environmental health (6.2%), and attractiveness of the streets (2.6%).The study concluded that the street sweeping programme has made the streets sanitary and aesthetically pleasing, provided employment and raised public perception of Ado-Ekiti as a clean and healthy city. Employment of more sweepers, provision of adequate equipment, public sensitisation and attitudinal change, enforcement of environmental sanitation laws, and improved remuneration will make street sweeping a sustainable waste management strategy in Ado-Ekiti. "